Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1017/s0007114511004776
|View full text |Cite
|
Sign up to set email alerts
|

Water balance throughout the adult life span in a German population

Abstract: Mild dehydration, defined as a 1-2 % loss in body mass caused by fluid deficit, is associated with risks of functional impairments and chronic diseases. Whether water requirements change with increasing age remains unclear. Therefore, the aim of the present investigation is to quantify hydration status and its complex determining factors from young to old adulthood to analyse age-related alterations and to provide a reliable database for the derivation of dietary recommendations. Urine samples collected over a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
73
2
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 25 publications
3
73
2
7
Order By: Relevance
“…This is in agreement with other studies evaluating fluid intake in other populations (30)(31)(32). However, in our study, the percentage of men who met the EFSA recommendations was similar to the percentage of women (63.3% of men, 62% of women).…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with other studies evaluating fluid intake in other populations (30)(31)(32). However, in our study, the percentage of men who met the EFSA recommendations was similar to the percentage of women (63.3% of men, 62% of women).…”
Section: Discussionsupporting
confidence: 93%
“…Compared to other biomarkers, FWR has the advantage of considering the maximum capacity of kidney concentration and, in addition, it takes into account a safety margin to ensure adequate hydration (9). The prevalence of inadequate hydration status is higher than the one reported by Manz in German children, although the mean 24 h urine osmolality (667 mOsm/kg in boys and 585 mOsm/kg in girls), an indirect parameter of hydration status, was similar to those described for German children (13), probably reflecting higher non-renal water losses by Portuguese children.…”
Section: Discussionmentioning
confidence: 99%
“…Friedrich Manz, a brilliant German researcher who proposed the free water reserve algorithm, argued that it was not possible to define a physiological or natural narrow urine osmolality range as it is always influenced by cultural context, namely food habits. This author suggested that only after additionally considering 24 h urine volume, urine solute excretion and maximum urine osmolality, it would be possible to quantify the individual 24 h hydration status (9).…”
Section: Discussionmentioning
confidence: 99%
“…This assumption was questioned repeatedly in the past, as mean urine volume of adults may easily amount to 2 L/day and more [18,[30][31][32]. Accordingly, in a very recent investigation of iodine status in Switzerland, median iodine concentration (measured in 1420 24-h urines) was only 60-70 µg/L, whereas 24-h iodine excretion indicated risk of inadequate iodine status in only 2 % of men and 14 % of women [31].…”
Section: Discussionmentioning
confidence: 99%
“…Present data basis for adult 24-h creatinine excretion reference values was the 24-h creatinine excretion data from the German VERA study [18][19][20]. The VERA study (Verbundstudie Ernährungserhebung und RisikofaktorenAnalytik) was a representative subsample taken randomly from the first National Food Consumption Survey (NVS I) of the Federal Republic of Germany (1986 and 1988), comprising 2006 subjects, aged 18-88, of whom each subject collected one 24-h urine sample.…”
Section: Estimation Of 24-h Iodine Excretion From Iodine Concentratiomentioning
confidence: 99%